Flora of the Serra do Cipó, Minas Gerais: Myristicaceae - Lopes, David Lucas Amorim; Correa, Tabata Alves; Lírio, Elton John de (Boletim de Botânica da Universidade de São Paulo, 2022)
Myristicaceae (Magnoliales) has c. 20 genera and 500 species, with tropical and subtropical distribution around the globe. This study aims to elaborate the taxonomic treatment of the family within the scope of the project “Flora da Serra do Cipó, Minas Gerais”. Myristicaceae is represented in the region by a single species, Virola bicuhyba, endemic to the Atlantic Forest. Morphological description, illustrations and comments for the species are presented.